2013
DOI: 10.1111/1471-0307.12099
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of a cell‐free extract of lactic acid bacteria entrapped in yeast to enhance flavour development in Cheddar cheese

Abstract: A lactococcal cell‐free extract (CFE) was successfully entrapped in freeze‐dried attenuated yeast. The entrapment process involved passive diffusion of enzymes from the CFE into the yeast during hydration. The entrapped CFE was subsequently added during Cheddar cheese production and its impact on a range of ripening parameters compared to added attenuated yeast or CFE alone. Statistically significant differences were evident for secondary proteolysis, sensory attributes and volatiles, which were related to enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
(75 reference statements)
0
9
1
Order By: Relevance
“…Compared with CC, all the enzyme activities were higher in the cheeses made with CFE. The highest (P < 0.05) differences were found after 30 d. These findings were in contrast with those reported in other studies, where no significant differences were found when commercial enzymes or CFE were used for cheesemaking (Yarlagadda et al, 2014). Losses of en-zymes in the drained whey (Wilkinson and Kilcawley, 2005) or the inherent instability of such enzymes under cheese ripening environmental conditions (Sheehan et al, 2009) may be the causes for these different behavior.…”
Section: Proteolysiscontrasting
confidence: 66%
See 3 more Smart Citations
“…Compared with CC, all the enzyme activities were higher in the cheeses made with CFE. The highest (P < 0.05) differences were found after 30 d. These findings were in contrast with those reported in other studies, where no significant differences were found when commercial enzymes or CFE were used for cheesemaking (Yarlagadda et al, 2014). Losses of en-zymes in the drained whey (Wilkinson and Kilcawley, 2005) or the inherent instability of such enzymes under cheese ripening environmental conditions (Sheehan et al, 2009) may be the causes for these different behavior.…”
Section: Proteolysiscontrasting
confidence: 66%
“…This is one of the main prerequisites to successfully use CFE. As recently shown (Nongonierma et al, 2013;Yarlagadda et al, 2014), the gross composition of Cheddar cheese did not vary when CFE from lactic acid bacteria were entrapped in yeasts or encapsulated in liposomes to enhance flavor development. The pH values of all ewe milk cheeses markedly decreased from the curd during manufacture (average value of 6.76) to 1 d of ripening (average value of 5.25), then it slightly varied.…”
Section: Cheese Manufacturing and Compositional And Microbiological Amentioning
confidence: 59%
See 2 more Smart Citations
“…The order of the presentation of all test samples was randomized to prevent first-order and carryover effects, and all samples were presented in duplicate. The assessors then participated in ranking descriptive analysis (Cavanagh et al, 2014;Yarlagadda et al, 2014;Fellendorf et al, 2016) using the consensus list of sensory descriptors provided to them, which was also measured on a 10-cm line scale. All samples were again presented in duplicate (Stone et al, 2012a).…”
Section: Hedonic Sensory Analysis and Ranking Descriptive Analysis Ofmentioning
confidence: 99%